The Important of Horizontal Directional Drilling Standard Technical Requirements - Abdul Aziz, Abdullah; Md Salleh, M.N; Azam Haron, N.; Zulhaidi Mohd Shafri, H; Fadzilah Ahmad, N (2019)
Horizontal Directional Drilling (HDD) is a trenchless technology provides an installation alternative that offers a lot of benefit compared to traditional open-cut method. It's called HDD because its steering ability to avoid existing utilities or other obstacles either horizontally, vertically and even pulled back where she got its name. HDD was developed in California in the 1970s and was introduced in Europe in 1986. Since year 1992 up to 2016 there are more than 40 thousand-unit HDD machine were sold worldwide. The aims of this study are to determine the present local authorities' technical requirements in HDD works, to determine the factors of HDD good practices and to develop a standard HDD's technical requirement. This research shall use mixed method in achieving the objectives. A descriptive and exploratory research design will be used for the study. The research design for this study contains the following consist of the research problem and research questions, sampling design, method of data collection, method of data analysis, validation/verification of the HDD standard technical requirements and its' frameworks. This study shall able to produce a standard HDD technical requirement and its' framework. With the establishment of a thorough and a standard local authority' technical requirements it's will able to educate the HDD contractors and assist them in carrying out their work properly, successfully and safely. It's will also able to educate the stake holders on how important to follow the stipulated technical requirements that contributed to the project success.